In Depth Analysis of a Sediment Core from North Aegean Sea - Mitsios, Iason; Pappa, Filothei; Patiris, Dionisis; Rouni, Panagiota; Anagnostakis, Marios; Tsabaris, Christos (HNPS Advances in Nuclear Physics, 2022)
In this work a thorough analysis of the vertical distribution of natural and artificial radionuclides and trace elements in a sediment core sample was conducted. A sediment core of 39 cm length was grabbed from the deep-sea trench (1540 m depth) southern of Samothrace Island, Aegean Sea. The sediment core was then treated at the Hellenic Centre for Marine Research, separated at 1cm increment samples, ranging from 0cm to 39 cm, dried, and milled. A first analysis of the samples was also conducted at HCMR using gamma spectroscopic techniques. Further spectroscopic analysis continued at Nuclear Engineering Department of the National Technical University of Athens (NED-NTUA) using an Extended Range Germanium Detector. The following radionuclides were determined 210Pb, 234Th, 226Ra, 228Ra, 228Th, 137Cs and 40K. Additionally, Instrumental Neutron Activation Analysis was used and the following major and trace elements were identified and quantified: Al, V, La, Sc, Mn, As, Ga, Cr, Zn, Co, Rb, Fe, K, Na and Ce. Based on the analysis of each sample, the vertical distribution of most natural radionuclides showed no significant variation. The vertical distribution of anthropogenic 137Cs was very low and almost constant. Unsupported 210Pb activity was about six times higher than 226Ra, indicating high radon fluxes. Furthermore, neutron activation analysis results indicate that almost all elements are within the expected range based on literature, while K and Na show a slightly increased concentration. For the area, these findings indicate steady and calm sedimentation processes.